Motion – Prophylactic Banding of Esophageal Varices Is Useful: Arguments against the Motion. (2002) - Kowdley, Kris V
Abstract : Bleeding from esophageal varices leads to substantial morbidity and mortality. Despite advances in pharmacological and endoscopic therapy, as well as general supportive care, the mortality rate associated with acute variceal hemorrhage has not improved significantly over the past two decades. Prophylactic therapy with nonselective beta-blockers or long acting nitrates reduces the incidence of variceal bleeding in patients with cirrhosis, is cost effective and may improve survival. Surgical portosystemic shunting reduces the risk of bleeding but is associated with significant operative mortality and a high risk of portosystemic encephalopathy. Endoscopic sclerotherapy causes adverse effects in a large proportion of patients and is, therefore, not suitable for primary prophylaxis of bleeding. Although variceal band ligation is effective in reducing the rate of bleeding and is safer than sclerotherapy, it has not been shown to provide a survival advantage compared with beta-blockers. A significant reduction in the rate of variceal bleeding with band ligation, compared with beta-blockers, was shown in only one study. Beta-blockers offer several advantages, including low cost, ease of use and safety. The available data do not yet support the prophylactic use of variceal band ligation, and this procedure should be reserved for patients who are either unwilling or unable to take beta-blockers. It is hoped that additional large, multicentre trials of band ligation versus beta-blockers will examine the efficacy, cost effectiveness and impact on quality of life among patients with cirrhosis.